Isolasi dan Seleksi Lactobacillus yang Berpotensi sebagai Agensia Probiotik - Siti Nur Purwandhani; Endang Sri Rahayu (agriTECH, 2003)
Lactic acid bacteria are important in food fermentation, in producing antimicrobial substances responsible for food preservation, and in balancing the microflora composition in gastrointestinal tract which contributing many healthful benefits (as probiotic agent). Disturbance due to pathogenic bacteria colonization in intestine as well as sterilisation of intestine due to antibiotic ingestion can be overcome by consumption of probiotic lactic acid bacteria. The objective of this study was to isolate Lactobacillus which potential for probiotic agent from intestinal material of healthy infant baby. Isolation was conducted using peptone glucose yeast extract media added with 0,2 % oxgall at pH 5, followed by incubation at 37 0C for 48 hr. Identifications were carried out based on Grain, morphological, biochemical and physiological characters, peptidoglycan types and protein profile on SDS-PAGE. Selection of probiotic agents were on based their antagonisms toward pathogenic bacteria, their resistance to antibiotics, and their survival at different oxygen availabilities. Based on morphological, biochemical and physiological characters among 12 lactobacilli strains obtained during isolation, 8 of them were identified as Lactobacillus acidophilus and the rest as Lactobacillus reuteri. However based on protein profile, L. acidophilus group has two different profiles, the first, consist of 7 strains and the second, consists of one strain. All isolates inhibited the growth of pathogenic bacteria including Shigella sp., Escherichia coli sp., Escherichia coli FNCC 009 I, Proleus sp., Salmonella choleraesius JCM 3919, Staphylococcus aureus FNCC 0047, Vibrio parahaemoliticus JCM 2147, Bacillus cereus ATCC 0057 and Listeria monocytogenes ATCC 7644, as shown by the inhibition zone ranging from 0,5-8 mm. Eight isolates of L. acidophilus were not resistant to antibiotics tested, while 3 isolates of L. reuteri were not resistant to chloramphenicol, rifampin and ampicillin, however they were resistant to tetracycline and elkosin. At reduced oxygen and anaerobic conditions all the isolates grew well, but at aerobic condition the growth was relatively slow. Strains of Lactobacillus acidophilus could be used for probiotic agents.